PERANCANGAN RESORT WISATA PANGURURAN DENGAN TEMA TRANSFORMASI ARSITEKTUR BATAK TOBA - Sigalingging, Hernandes; Sihombing, Sanggam B; Mayono Suko Marbinoto , (Jurnal Sains dan Teknologi ISTP, 2024)
Pangururam is one of the sub-districts of Samosir District. Tourism in Panguruland and Lake Toba is very good. Tourism development is needed to support visitors to Samosir Island. One of them is to develop tourism through the construction of Pangululan tourist resort. How to use the Toba Batak Architectural Transformation theme using the theme. This can also be used to maintain sustainability or introduce tourists to the Toba Batak area The theme of the Pangurulan Tourist Resort architecture is "Transformation" by Toba Batak Architects. With this resort, maintaining the form of traditional Batak buildings or introducing them to tourists could be a solution. Through this resort you can also be introduced to typical Toba Batak dishes. Pangululan Tourist Resort is a tourist resort that does not eliminate the traditional characteristics of Toba Batak and adopts the theme of Toba Batak architectural renovation. With the presence of this resort, it is also expected to boost the economic development of the Pangululam region.